Synergistic Trial Model of Four Coadministration of Medicinal Herbs on Malaria infected Mice - AA Anigboro (Journal of Applied Sciences and Environmental Management, 2018)
Azadirachta indica (neem tree), Vernonia amygdalina (bitter leaf), Eucalyptus camaldulensis (red gum), and Bambusa vulgaris (bamboo) are locally employed for the management of malaria infection. This study examined the synergistic action of these four co-administered aqueous leaf extracts on malaria infected mice. There was a noticeable reduction in the parasitemia levels from 62 to 8% when the administration of the extracts given. The electrolytes (sodium, calcium, phosphorus and chloride) levels in the serum returned close to normal in the treated animals. There was a marked difference in alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and gamma glutamyl-transferase (GGT) activities in serum of the treated mice in comparison with the control groups (P<0.05). Total and direct bilirubin levels also increased in animals treated with the extract the activity of antioxidants enzymes such as glutathione transferase (GST), catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD) of the treated animals increased relative to the control groups (P<0.05). Glutathione (GSH) levels increased upon the intake of the extract by the groups treated extract. The levels of lipid peroxidation (MDA) and nitric oxide (NO) reduced in animals treated with the extract. Urea, creatinine and uric acid in the serum were brought towards normalization after the intake of the various extracts. These observations are indication of antimalarial and protective roles of the four co-administered extracts on parasitized mice.